SISTEM KONTROL SUN SEEKER SUATU MODEL UNTUK MENGENDALIKAN PERILAKU WAHANA ANTARIKSA - Purwanto, Eko Budi (Indonesian Journal of Aerospace, 2007)
Sun seeker control system doing by monitoring the sun as main reference. The result of monitoring the sun position used for the line correction of space vehicle. In these paper used simulation method for gated parameter value control system. To know the influence of sun seeker control system, simulation was doing with and without lead compensator. The result of simulation show that without sun seeker control system the time settling is ts = 0.35 second and maximum overshoot Mp = 44,4 percent. These results not reasonable for controling of plan with high velocity like rocket and satellite. Later simulation with phase lead sun seeker control system, give settling time ts = 0,12 second and maximum overshoot Mp 5 percent. From the simulation data that sun seeker control system can used for space vehicle control and agree with steady state error specification.Keywords: Sun seeker control system, FFase lead, Waktu penetapan, lewatan maksimum, kondisi tunak